2021
DOI: 10.7759/cureus.20728
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Permanent Vascular Access Formation and Referral to a Nephrologist in Incident Hemodialysis Patients: A Single Center Experience

Abstract: Objective: This study assessed the factors associated with delayed referral to a nephrologist and delay in formation of a permanent vascular access in incident hemodialysis (HD) patients. Methods: This prospective cross-sectional study was conducted from February 2021 to July 2021 on end stage renal disease (ESRD) patients receiving maintenance hemodialysis (MHD) at our center. Data were collected at the bedside during the HD session about a referral to a nephrologist, about when they were asked for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Only 8% of patients developed distal latero-terminal radiocephalic fistula (DLTRC) -Figure 1. native fistula [6]. Careful preoperative clinical and instrumental evaluation is required to decide both the site and type of anastomosis.…”
Section: Resultsmentioning
confidence: 99%
“…Only 8% of patients developed distal latero-terminal radiocephalic fistula (DLTRC) -Figure 1. native fistula [6]. Careful preoperative clinical and instrumental evaluation is required to decide both the site and type of anastomosis.…”
Section: Resultsmentioning
confidence: 99%
“…The 2022 ADA guidelines and KDIGO CKD Working Group recommend that patients with advanced kidney disease (eGFR < 30 mL/min/1.73 m 2 ) also be referred to a kidney specialist. 61 , 62 …”
Section: Timely Diagnosis Of Ckd Requires Effective Multidisciplinary...mentioning
confidence: 99%
“…The 2022 ADA guidelines and KDIGO CKD Working Group recommend that patients with advanced kidney disease (eGFR < 30 mL/min/1.73 m 2 ) also be referred to a kidney specialist. 61,62 The ADA notes that, despite recommendations for early referral, there are additional factors that influence the decision for primary care clinicians to refer patients, which may not always make early referrals feasible. 63 Study results from an US academic healthcare system found that only 45.4% of patients actively visiting their primary care clinicians are referred to a nephrologist, but the study did not specify whether patients who were referred had an eGFR < 30 mL/min/1.73 m 2 .…”
Section: Timely Diagnosis Of Ckd Requires Effective Multidisciplinary...mentioning
confidence: 99%